(untitled) (Damu Journal of Sport Sciences, 2024)
The problem of the research is that there are many players who take the hormone Testosterone in an unscientific and studied manner, which is clearly evident in their external appearances of pimples on the face and body, high temperatures, hysteria, nervous conditions, heart problems and kidney problems. Therefore, the researcher decided to study this case of bodybuilders by conducting scientific laboratory analyses to document the most important hormonal problems that affect these players. The research aims to identify the effect of training using the hormone Testosterone on some physiological measurements of the kidneys of bodybuilders The researcher used the experimental method using the two-group method. The research community and sample were represented by a group of 14 bodybuilders who attend gyms. After using research procedures through pre-tests and measurements, conducting training, and then post-tests and measurements, and after conducting statistical treatments, a set of important conclusions appeared to us that serve the training and health process of bodybuilders, including that there is superiority for the group that uses the hormone Testosterone. It appeared to us that the group that used the hormone had affected the kidneys through swelling and the abundance of impurities that appeared through the analyses that were conducted on them.